Classical and alternative activation and metalloproteinase expression occurs in foam cell macrophages in male and female ApoE null mice in the absence of T- and B-lymphocytes - Hayes, Elaine M.; Tsaousi, Aikaterini; Di Gregoli, Karina; Jenkinson, S R.; Bond, Andrew R.; Johnson, Jason L.; Bevan, Laura; Thomas, Anita C.; Newby, Andrew C. (Frontiers in Immunology, 2014)
Background: Rupture of advanced atherosclerotic plaques accounts for most life-threatening myocardial infarctions. Classical (M1) and alternative (M2) macrophage activation could promote atherosclerotic plaque progression and rupture by increasing production of proteases, including matrix metalloproteinases (MMPs). Lymphocyte-derived cytokines may be essential for generating M1 and M2 phenotypes in plaques, although this has not been rigorously tested until now. Methods and results: We validated the expression of M1 markers (iNOS and COX-2) and M2 markers (arginase-1, Ym-1, and CD206) and then measured MMP mRNA levels in mouse macrophages during classical and alternative activation in vitro. We then compared mRNA expression of these genes ex vivo in foam cells from subcutaneous granulomas in fat-fed immune-competent ApoE knockout (KO) and immune-compromised ApoE/Rag-1 double-KO mice, which lack all T and B cells. Furthermore, we performed immunohistochemistry in subcutaneous granulomas and in aortic root and brachiocephalic artery atherosclerotic plaques to measure the extent of M1/M2 marker and MMP protein expression in vivo. Classical activation of mouse macrophages with bacterial lipopolysaccharide in vitro increased MMPs-13, -14, and -25 but decreased MMP-19 and TIMP-2 mRNA expressions. Alternative activation with IL-4 increased MMP-19 expression. Foam cells in subcutaneous granulomas expressed all M1/M2 markers and MMPs at ex vivo mRNA and in vivo protein levels, irrespective of Rag-1 genotype. There were also similar percentages of foam cell macrophages (FCMs) carrying M1/M2 markers and MMPs in atherosclerotic plaques from ApoE KO and ApoE/Rag-1 double-KO mice. Conclusion: Classical and alternative activation leads to distinct MMP expression patterns in mouse macrophages in vitro. M1 and M2 polarization in vivo occurs in the absence of T and B lymphocytes in either granuloma or plaque FCMs.